Stability Constants of Transition Metal Complexes of 2-Hydroxybenzilidine-p-Chloroaniline - Desai, Pulkeshi; Agarwal, Balkrishna; Barot, Girish; Nayak, Gauri; Mangaonkar, Kiran (Asian Journal of Chemistry, 2010)
Proton dissociation constant of the ligand and the stability constants of the complexes of the metal ions Co(II), Ni(II), Cu(II) and Zn(II) with 2-hydroxy- benzilidine p-chloroaniline have been determined potentiometrically at 30 ± 0.1ºC and at ionic strength 0.1 M in 75 : 25 (v/v) dioxane-water medium, log K1 and log K2 values have been determined. The stabilities of the chelates follow the order Zn > Co > Cu > Ni.